After the Revolution: An Alternative Future for Atlantic History. Issue 3 (March 2014) - Prior, David
Abstract This essay argues for a reframed Atlantic history that abandons the concept of the "Atlantic World." Though bold and creative, the Atlantic World concept has mired the field of Atlantic history in an unnecessary debate about that world's alleged coherence and distinctiveness. By foregrounding the tensions between these two criteria, this article offers a critique of the Atlantic World concept that goes beyond the often trenchant but nonetheless piecemeal criticisms that have been levied to date. In addressing these tensions, the goal of this article is not to condemn the broader enterprise of Atlantic history, but rather to call attention to an alternative formulation of it. We can practice Atlantic history without the Atlantic World concept because of two conditions that hold for much of early‐modern and modern history. First, from European maritime expansion on, connections across and around the Atlantic proliferated in ways that were neither natural nor inevitable. Second, the creation and severing of earlier connections tended to shape later ones in profound and perplexing ways. Atlantic history can serve as the field where diverse scholars pool their expertise to assess the relationships among these connections over time.